2021
DOI: 10.26656/fr.2017.5(5).470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hot water treatment to quality properties of pineapple (Ananas comosus) fruit during storage

Abstract: Pineapple (Ananas comosus) was a non-climacteric fruit popularly distributed in Vietnam and other tropical regions. It was highly preferred by great appearance, wonderful texture, special flavour and perfect nutritional value. Moreover, it was also a good source of minerals, vitamins and antioxidants beneficial for human health. In harvesting season, it was highly perishable under ambient storage due to its high metabolic and moisture content resulting in quality degradation. This research evaluated the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The sample was then stored at room temperature and stored at a cold temperature of about 5 °C [6]. Observations were made every day for 6 days which included the following variables: weight loss [7], acidity level [8], fruit color scale index [9], vitamin content C [10].…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was then stored at room temperature and stored at a cold temperature of about 5 °C [6]. Observations were made every day for 6 days which included the following variables: weight loss [7], acidity level [8], fruit color scale index [9], vitamin content C [10].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Weight loss value was obtained by comparing the weight of fruit on day n with fruit weight on day (n−1) [7]. Measurement of weight loss was carried out by weighing using an analytical balance.…”
Section: Pineapple Weight Lossmentioning
confidence: 99%
“…Hot water treatment could reduce disease incidence and maintain postharvest quality during storage and prolong the shelf-life of papaya fruit [34]. Extended storage stability and marketability was reported for Pineapple and avocado fruits treated by hot water at different temperature and time combination [35,36]. Related research finding revealed that Guava fruits treated with hot water at 45 o C for 3 minute lasts upto 31 days under room temperature of 5±2 o C and 85 to 90 per cent relative humidity [37].…”
Section: Calcium Chloride Treatmentsmentioning
confidence: 99%